Wrongful allegations of sexual and child abuse - Burnett, Ros (Oxford : Oxford University Press, 2016)
This work brings together contributions by academics and experts from different disciplinary backgrounds focused on false allegations of recent or historical abuse. The adjective 'false', used interchangeably with 'wrongful', includes allegations made in error as well as those which are deliberate fabrications or distortions of the truth.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 5, 2016).
Keywords: Sex crimes; Child abuse; True Crime